PO065 Headache at whipps cross university hospital: a retrospective audit from 2010–2013. (1st December 2017) - Jacobs, Benjamin; Ratnajothy, Saiesvaran; Egerton, Chloe; Baptiste, Patrice; Bahra, Anish
Abstract : Headache is the most common reason for referral to neurology clinics in the UK. Guidance exists for managing and referring headache. In 2012, a management strategy was sent out to patients and local GPs by Whipps Cross headache clinic. To evaluate the efficacy of this intervention, clinic letters from 2010–2013 were retrospectively analysed. Full information was available for 332 patients. Chronic and episodic migraine were the most common diagnoses made at clinic (29.8% and 37.6% prevalence respectively). From 2010 to 2013, the prevalence of chronic migraine increased while the prevalence of episodic migraine decreased. The prevalence of non-migraine headache increased from 17.8% in 2010 to 32.7% in 2013. The mean prevalence of medication overuse headache was 34.6% and did not vary substantially between 2010 and 2013. The prevalence among patients with chronic migraine was 71.7%. Preventative use was recorded for 41.4% of patients with chronic migraine and 24.0% of patients with episodic migraine. 14.0% of 2010 referrals led to further neuro-imaging compared with 21.8% in 2013. No scans demonstrated pathology relevant to the presentation. Further improvements are therefore required to ensure that headache clinic time is used effectively and to promote the management of episodic migraine in primary care.